Minimal change disease associated with balsalazide therapy for ulcerative colitis - Ahmad M. Al-Taee; Sami A. Almaskeen; Farrukh M. Koraishy (Society of Diabetic Nephropathy Prevention, 2019)
Introduction: 5-aminosalicylic acid (5-ASA) compounds have been used in the management of ulcerative colitis for decades. Nephrotoxicity has been previously described in patients treated with 5-ASA compounds and usually manifests as interstitial nephritis, however a few cases of nephrotic syndrome have been reported. Balsalazide is a pro-drug composed of 5-ASA linked to an inert carrier. Case Presentation: Here we report the case of a 74-year-old man with a history of ulcerative proctosigmoiditis treated with balsalazide who presented to our clinic with bilateral lower extremity edema three months after initiation of balsalazide. Laboratory workup showed nephrotic range proteinuria without an apparent secondary etiology. Given worsening proteinuria and renal function despite cessation of balsalazide, the patient underwent renal biopsy that revealed minimal change disease. High dose steroids were started and complete remission of proteinuria was achieved one month into therapy which was slowly tapered over the next five months. Eventual resolution of edema and return of creatinine back to patient's baseline level was achieved. Conclusion: To our knowledge, this is the first report of nephrotic syndrome manifesting soon after initiation of balsalazide therapy. Our work highlights the importance of maintaining a high clinical suspicion for nephrotoxicity when using balsalazide.